THEORETICAL FOUNDATIONS OF STUDYING CHILDREN’S GAMES IN ENGLISH AND UZBEK FAIRY TALES - Muhammadjonova Ma'muraxon Muhsinjon qizi,; Otabek Mukhamadovich Fayzulloyev., (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  This  article  explores  the  theoretical  foundations  of  studying children’s games in English and Uzbek fairy tales. It examines the role of play as a cultural and pedagogical phenomenon reflected in folklore and analyzes how games function as symbolic elements within narratives. The study highlights the educational, moral, and social values transmitted through children’s games and their significance in shaping  cultural  identity  across  generations.  By  comparing  English  and  Uzbek traditions, the article provides insights into both universal and culture-specific aspects of  play  in  folklore,  offering  a  deeper  understanding  of  how  fairy  tales  integrate entertainment with moral and educational purposes.